Pengaruh Literasi Keuangan dan Financial Technology Terhadap Inklusi Keuangan pada Masyarakat Pekanbaru (Studi pada Investor Saham Syariah di Pekanbaru) - Yolanda Atika Safira; Yulia Efni; Fitri Fitri (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
This study aims to examine the effect of financial literacy and the use of online trading applications on financial inclusion of sharia stock Investors in Pekanbaru. The sample used in this study was 150 sharia stock Investors in Pekanbaru who use online trading applications in stock transactions. Sampling uses non-probability sampling methods and purposive sampling techniques. The data in this study are quantitative data obtained using a questionnaire and processed by using Partial Least Square Structural Equation Modeling (PLS-SEM). The results of this study indicate that financial literacy has a positive and significant effect on financial inclusion of sharia stock investors in Pekanbaru and financial technology has a positive and significant effect on sharia stock investors in Pekanbaru.